Operando monitoring of the solution-mediated discharge and charge processes in a Na-O2 battery using liquid-electrochemical Transmission Electron Microscopy - Lutz, Lukas; Dachraoui, Walid; Demortière, Arnaud; Johnson, Lee R.; Bruce, Peter G.; Grimaud, Alexis; Tarascon, Jean-Marie (American Chemical Society, 2018)
Despite the fact that in sodium-oxygen (Na-O2) batteries show promise as high-energy storage systems, this technology is still the subject of intense fundamental research, owing to the complex reaction by which it operates. To understand the formation mechanism of the discharge product, sodium superoxide (NaO2), advanced experimental tools must be developed. Here we present for the first time the use of a Na-O2 micro-battery using a liquid aprotic electrolyte coupled with fast imaging transmission electron microscopy to visualize, in real time, the mechanism of NaO2 nucleation/growth. We observe that the formation of NaO2 cubes during reduction occurs by a solution-mediated nucleation process. Furthermore, we unambiguously demonstrate that the subsequent oxidation of NaO2, of which little is known, also proceeds via a solution mechanism. We also provide insight into the cell electrochemistry via the visualization of an outer shell of parasitic reaction product, formed through chemical reaction at the interface between the growing NaO2 cubes and the electrolyte, and suggest that this process is responsible for the poor cyclability of Na-O2 batteries. The assessment of the discharge- charge mechanistic in Na-O2 batteries through operando electrochemical TEM visualization should facilitate the development of this battery technology.